At-risk Internet addiction and related factors among junior high school teachers-based on a nationwide cross-sectional study in Japan - Ayumi Iwaibara; Mari Fukuda; Hideki Tsumura; Hideyuki Kanda (Komiyama Printing Co. Ltd, 2019)
Abstract Background School teachers have a possibility toward at-risk Internet addiction (IA) due to increased opportunities to use the Internet, along with the spread of the Internet in recent years. Burnout syndrome (BOS) is found to be one of the symptoms related to unhealthy mental health, especially among teachers. This study aims to research the relationship between at-risk IA and the Internet usage or BOS by conducting a nationwide cross-sectional survey and examining the factors associated with IA. Method This study was a cross-sectional survey by anonymous questionnaire. This survey was a random sampling survey of junior high schools across Japan in 2016. The participants were 1696 teachers at 73 schools (response rate in teachers 51.0%). We asked participants for details of their backgrounds, Internet usage, the Internet Addiction Test (IAT) by Young, and the Japanese Burnout Scale (JBS). We divided the participants into either the at-risk IA group (IAT score ≧ 40, n = 96) or the non-IA group (IAT score < 40, n = 1600). To compare the difference between at-risk IA and non-IA, we used nonparametric tests and t test according to variables. To analyze the relationship between the IAT score and the scores of three factors of the JBS (emotional exhaustion, depersonalization, and personal accomplishment), we used both ANOVA and ANCOVA, adjusted by relevant confounding factors. To clarify the contribution of each independent variable to IAT scores, we used multiple logistic regression analysis. Results In our study, at-risk IA was associated with using the internet many hours privately, being on the Internet both on weekdays and weekends, playing games, and surfing the Internet. In the relationship between IAT score and BOS factor score, a higher score for "depersonalization" had a positive relationship with at-risk IA, and the highest quartile for "decline of personal accomplishment" had a lower odds ratio with at-risk IA by multiple logistic regression analysis. Conclusion We clarified there is a significant relationship between at-risk IA and BOS among junior high school teachers in a nationwide survey. Our results suggest that finding depersonalization at the early stage may lead to the prevention of at-risk IA among teachers. Those who are at-risk of IA may feel personal accomplishment through use of the Internet.